After all, in reality nature cannot create itself! (Once again about the true mechanisms of evolution) - Ashursky, Emir E. (Cognition, 2023)
How much long the human civilization exists on Earth, so much time there are practically continuous disputes between supporters of creationism and evolutionism. At that in corresponding arguments, the former usually emphasize the astonishing complexity of live systems what's deliberately thereby associated with a pretty far-fetched chance of their self-emergence. While the latter flaunt about own totally unbiased reasoning which doesn’t require introduction of additional entities. Insofar as, to a certain extent, both of them prove to be right, so having analyzed all the scientific information at our disposal, we decided that it would be correct to try anyway to combine these, at first gaze, opposite ideas into a single whole. Thus, if to resume here the most important cornerstone points on which the author relies, justifying his view over organismic evolution, then one should indicate as follows. Conceptually quite valid possibility of significant outwardly visible changes at the level of an individual – along with a strict karyotypic constancy in all its foreseeable ancestors. The dominant role of the factors of internal self-development and selection as the main driving arms of progress. The complete autonomy of the above evolutionary postulates from blind mutational entropy, i.e. the obvious independence of these routes from each other. In this way, the bold original theory presented in given article is based, by and large, just on those "three pillars".